Are the Modern Diets for the Treatment of Obesity Better than the Classical Ones? - Chrysi C. Koliaki; Nicholas L. Katsilambros (Endocrines, 2022)
Conventional hypocaloric diets, providing continuous energy restriction, are considered to be the cornerstone of dietary management of obesity. Although energy-restricted diets are overall safe, healthy, and modestly effective, their long-term adherence is difficult to accomplish. Intermittent fasting and ketogenic diets have emerged as attractive alternative dietary options for weight loss and improvement in cardiometabolic risk. Intermittent fasting is a unique dietary pattern characterized by periods of eating alternated with periods of fasting. Ketogenic diets are very low in carbohydrate, modest in protein, and high in fat. Several systematic reviews and meta-analyses of randomized controlled trials (RCTs) have reported beneficial but short-lived effects of intermittent fasting and ketogenic diets on various obesity-related health outcomes. Although for both diets, the current evidence is promising and steadily evolving, whether they are better than traditional calorie-restricted diets, whether they can safely lead to sustained weight loss and overall health benefits, and their effects on body composition, weight loss maintenance, energy intake and expenditure, diet quality, and cardiometabolic risk factors are still not unequivocally proven. The aim of the present review is to summarize the current state of evidence regarding the effects of these two popular modern diets, namely intermittent fasting and ketogenic diets. We describe the rationale and characteristics of different dietary protocols, we analyze the major mechanisms explaining their weight loss and cardiometabolic effects, and we provide a concise update on their effects on body weight and cardiometabolic risk factors, focusing on meta-analyses of RCTs. We also discuss knowledge gaps in the field of these diets, and we indicate directions for future research.